Synthesis, Crystal Structures, and Luminescence and Magnetic Properties of 3D Chiral and Achiral Lanthanide Diphosphonates Containing Left- and Right-Handed Helical Chains - Dong, Da-Peng; Liu, Lei; Sun, Zhen-Gang; Jiao, Cheng-Qi; Liu, Zhong-Min; Li, Chao; Zhu, Yan-Yu; Chen, Kai; Wang, Cheng-Lin (Crystal growth & design, 2011)
Using the heptadentate ligand hedpH4 (1-hydroxyethylidenediphosphonic acid) and lanthanide chloride, two isomorphous series of coordination frameworks of the general formula [NH4][Ln(hedp)(H2O)]·H2O (series 1, orthorhombic P212121, Ln = La (1), Ce (2), Pr (3), Nd (4)) and [NH4][Ln(hedp)(H2O)] (series 2, orthorhombic Pnma, Ln = Sm (5), Eu (6), Gd (7), Tb (8), Dy (9), Y (10), Er (11)) have been assembled and characterized with IR, elemental analysis, thermogravimetric analysis, and single-crystal and powder X-ray diffraction methods. In both series, each inorganic chain based on LnO8 and CPO3 polyhedra are interconnected through phosphonate ligands to form chiral and achiral 3D open-framework structures with left- and right-handed helical chains. Meanwhile, the two series also exhibit two types of 3D framework structures with similar network topologies. The crystal water molecule plays an important role to induce chiral structure and affects the crystal packing of the molecules with extensive hydrogen bonding. The luminescence properties of compounds 5, 6, 8 and 9 and the magnetic property of compound 7 have also been studied.